GENDER BIAS AS REFLECTED ON UPIN & IPIN THE SERIES - Herry Nur Hidayat; Wasana Wasana (JENTERA: Jurnal Kajian Sastra, 2019)
This paper describes gender bias as reflected in Upin & Ipin the series. This study employed qualitative research methods in which the objects were observed repeatedly to construct indicators that reflected gender bias. Then it was followed by analyzing them within sociological and feminist perspectives. It showed that there was an imbalance in gender position within several episodes of Upin & Ipin. As one of the media forms that later on becoming an instructional media, it should posit its position neutrally in the term of gender issues. The content of the gender bias in Upin & Ipin reflected within characters and settings. It reflected as the characters articulate their dialogues and behave in their daily life. There was a tendency to determine the ownership of boys and girls based on colors and things. In this case, pink regarded as to belong to girls. Also, there was a tendency to describe that girls and boys behave differently. For example, girls should be gentle and neat, and boys should be strong and brave. In the term of setting, gender bias reflected in the domination of areas that boys dominate outdoor public space while girls are in the domestic sector (households). Abstrak: Artikel ini memaparkan hasil penelitian terhadap serial animasi Upin & Ipin yang memperlihatkan bias gender dalam beberapa episodenya. Sebagai salah satu bentuk media yang kemudian menjadi media pembelajaran seharusnya bisa berposisi netral dalam hal gender. Penelitian ini menggunakan metode penelitian kualitatif. Objek material diamati secara berulang untuk memperoleh indikator yang menunjukkan bias gender yang kemudian dianalisis dalam kerangka sosiologi dan perspektif feminisme. Hasil penelitian menunjukkan muatan bias gender dalam Upin & Ipin terdapat dalam tokoh dan penokohan serta pembentukan latar. Dalam tokoh dan penokohan serial animasi ini, melalui dialog dan lakuannya, terdapat kecenderungan “kepemilikkan” warna dan benda tertentu. Dalam hal ini, warna merah muda dianggap sebagai warna “milik” perempuan. Di samping itu, terdapat pula kecenderungan sifat dan perilaku perempuan dan laki-laki. Perempuan harus memiliki sifat lembut dan rapi sementara laki-laki harus keras dan berani. Dalam latar cerita, muatan bias gender muncul sebagai bentuk wilayah dominasi perempuan dan laki-laki. Perempuan dibatasi dalam wilayah domestik rumah tangga sementara laki-laki berada di wilayah luar (publik)..